Gesellschaftlicher und rechtlicher Status der Sprachmeister*innen in der Frühen Neuzeit. Sprachliche Fähigkeiten als entscheidendes Kriterium? - Vera Flatz (Historia.scribere)
Societal and Legal Status of Foreign Language Teachers in the Early Modern Age. Language Skills as the Determining Criterion?